The Effects of Consumption Value, Environmental Concerns, And Consumer Attitudes Towards Consumer Purchase Intentions of Electric Cars - Riptiono, Sulis (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
This study aimed to investigate the effects of consumption values, environmental concerns, and consumer attitudes towards consumer purchase intentions of electric cars. This research was conducted in Central Java, using 220 samples taken using purposive sampling technique. The analysis used with SEM-AMOS version 24. Based on the results of the study, the consumption value represented by social value variables, functional value quality and epistemic value revealed that social value and epistemic value can have an influence on environmental concern, while functional value quality is not able to provide influence on environmental concern. In addition, this study also revealed that the environmental concern variable is a major predictor of increasing consumer attitudes towards green products, but it does not have an effect on consumer purchase intentions. Furthermore, consumer attitudes towards green products are key in increasing consumer purchase intentions for electric cars. Keywords: consumption value, attitude, purchase intention, green products, electric car